The role of Kipchak in changing the geographical shape of the Eurasian steppe regions in VIII- XII centuries (Journal of history, 2020)
The article discusses the role of Kipchak in changing the geographical shape of the Eurasian steppe regions in VIII-XII centuries.Investigate the migration of nomads, Kipchak in the West  in the VIII-      XII centuries, and that they, in different historical periods, joining the vari- ous medieval states, have made their contribution to the establishment of their state. Also considered their role in  the  development  of  geographic and ethnic shape modern Turkic states.As a result, on the basis of historical sources and literature the author concludes that the geographic shape of Kipchak steppe was not stable and one of the reasons this was the nomadic life of Kipchak.